OPTIMIZING SOCIAL MEDIA-BASED GREEN MARKETING STRATEGIES TO ENHANCE CUSTOMER ENGAGEMENT: A CASE STUDY OF SARIAYU MARTHA TILAAR - Sekar Soraya Maheswari; Atik Aprianingsih (RADJA PUBLIKA, 2026)
This study will investigate the application of green marketing strategies via social media to improve the engagement of the customers of the Generation Z by taking Sariayu Martha Tilaar as a case study. Over the last few years the rapid adoption of digitalization in the Indonesian beauty industry has rendered the involvement in the social media a deciding factor in the competitiveness of the brands, especially among younger customers who place a strong value on authenticity, sustainability, and the speed of digital engagement. Although Sariayu has a high institutional credibility, a long history, and adherence to natural and ethical beauty, the brand has very poor results in digital performance. The theoretical model combines the Theory of Reasoned Action and the Stimulus-Organism-Response model and assumes that the Attitude Towards Engagement and Subjective Norms represent the variables. The quantitative approach is adopted with the help of the PLS-SEM and primary data would be gathered with 217 Gen Z and Millennial respondents. Such a methodological approach provides an opportunity to assess direct and indirect connections and determine whether social media marketing, online marketing, brand ambassadors, and brand community affect attitudes and subjective norms and whether these organism variables in turn prompt the engagement behavior. The empirical results demonstrate that there is Engagement Paradox. Even though the general model has a significant propensity to predict customer engagement, the psychological processes assumed to mediate the interrelationship do not take place. The engagement attitude and subjective norms do show a weak explanatory power and neither shows a significant effect in predicting engagement behavior. Some of the digital stimuli do not have a significant impact on the mediating variables as well. Interestingly, the brand community variable has a negative influence on the attitudes, which indicates the potential content fatigue or the sense of a lack of genuineness in the ongoing community-building efforts of Sariayu.